1972
DOI: 10.1126/science.175.4026.1122
|View full text |Cite
|
Sign up to set email alerts
|

Selenium: Relation to Decreased Toxicity of Methylmercury Added to Diets Containing Tuna

Abstract: Japanese quail given 20 parts per million of mercury as methylmercury in diets containing 17 percent (by weight) tuna survived longer than quail given this concentration of methylmercury in a corn-soya diet. Tuna has a relatively high content of selenium and tends to accumulate additional selenium when mercury is present. A content of selenium in the diet comparable to that supplied by tuna decreased methylmercury toxicity in rats. Selenium in tuna, far from being a hazard in itself, may lessen the danger to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
254
0
7

Year Published

1975
1975
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 613 publications
(272 citation statements)
references
References 7 publications
11
254
0
7
Order By: Relevance
“…In another model, quails given MeHg in diet containing tuna survived longer than quails given the same concentration of MeHg in a corn-soya diet, implying Se that was present in the tuna was responsible for this effect (Ganther et al, 1972). In a separate study in rats, Ganther et al (1972) showed that MeHg toxicity was decreased by the levels of Se in a diet that were comparable to that was supplied by tuna. In an in utero MeHg and Se study on mice, the group that was given the lowest amount of Se and the highest dose of MeHg was mostly adversely affected in neurobehavioral outcome (Watanabe et al, 1999).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…In another model, quails given MeHg in diet containing tuna survived longer than quails given the same concentration of MeHg in a corn-soya diet, implying Se that was present in the tuna was responsible for this effect (Ganther et al, 1972). In a separate study in rats, Ganther et al (1972) showed that MeHg toxicity was decreased by the levels of Se in a diet that were comparable to that was supplied by tuna. In an in utero MeHg and Se study on mice, the group that was given the lowest amount of Se and the highest dose of MeHg was mostly adversely affected in neurobehavioral outcome (Watanabe et al, 1999).…”
Section: Introductionmentioning
confidence: 85%
“…In contrast, numerous animal studies have reported that Se may decrease MeHg toxicity (Beyrouty and Chan, 2006;Ganther et al, 1972;Parizek and Ostadalova, 1967;Whanger, 1992). These experimental studies provide an understanding in how Se and MeHg may interact under different exposure regimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental models, selenium in seafood may attenuate methylmercury toxicity (15). Thus, seafood diets during pregnancy must be considered as a balance between the beneficial effect of essential nutrients and the adverse effects caused by toxicants.…”
Section: Steuerwald Et Almentioning
confidence: 99%
“…The protective action of sodium selenite against the nephrotoxic effect of inorganic mercury (13,(28)(29)(30)(31)(32)(33)(34) and the beneficial action of selenium in methylmercury poisoning has been described by many authors (33,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). Sodium selenite administration results in delayed occurrence of symptoms of neurological and histological disturbances and in enhanced life expectancy of exposed animals (40,43,48).…”
Section: Introductionmentioning
confidence: 99%